Measuring muscle oxygenation in endurance sports with wearable nirs - from validation to application - Yogev, A (University of British Columbia, 2023)
Muscle oxygenation monitoring is enabled by commercially available wearable near-infrared spectroscopy (NIRS) sensors. This technology is receiving greater attention from athletes, sports practitioners, and researchers. However, a more comprehensive understanding of its utility in sports applications and its validity and reliability in comparison with common internal load measures is desired. For my dissertation, I addressed unanswered questions related to the effect of endurance training on NIRS and the reliability and validity of wearable NIRS. Specifically, I conducted the following studies: (i) a meta-analysis on the effects of endurance training on muscle oxygenation response during an incremental exercise test (IET); (ii) a validation study utilizing wearable NIRS to assess the differences between the respiratory compensation point (RCP) and the deoxygenation breakpoints at the vastus lateralis (VL) and deltoid muscle during an IET; (iii) a study on the effect of high-intensity cycling bouts on muscle oxygenation, and the reliability of wearable NIRS between sessions; and (iv) a study comparing the reliability of muscle oxygenation against common physiological and performance measurements during an intermittent IET. The key findings from my dissertation were (i) following endurance training, the nadir in muscle oxygenation did not demonstrate a change over time during an IET. The relationship between changes in peak power output and a greater minimum muscle oxygen saturation showed a trend following endurance training. (ii) no significant difference between the RCP, and muscle deoxygenation breakpoint at the VL and deltoid muscles, but a large degree of individual heterogeneity existed; (iii) the wearable NIRS sensor yielded a heterogeneous muscle oxygenation response as expected during severe intensity interval exercise on a cycling ergometer, with good reliability between sessions in trained cyclists; and (iv) muscle oxygenation showed excellent to good test-retest reliability across intensities during an indoor cycling IET. Compared with systemic oxygen uptake and heart rate, muscle oxygen saturation showed comparable interclass correlations. Relative to blood lactate concentration and rating of perceived exertion, muscle oxygen saturation demonstrated better reliability across intensities. Altogether, this dissertation provides valuable insights into the utility of wearable NIRS in exercise and following endurance training interventions, relative to common physiological and performance measures.